Case reportCoreValve transcatheter aortic valve implantation complicated by stress cardiomyopathy (tako-tsubo) and septic shock - Kustrzycka-Kratochwil, Dorota; Makowska, Agata; Kübler, Piotr; Telichowski, Artur; Banasiak, Waldemar; Jankowska, Ewa; Ponikowski, Piotr; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Transcatheter aortic valve implantation (TAVI) has become a promising alternative for surgical therapy of patients with severe aortic stenosis. Transcatheter aortic valve implantation procedures are currently limited to patients who have been disqualified from surgery because of high operative risk, but they are associated with specific complications. We report a case of an 82-year-old woman undergoing TAVI. The patient was not considered as a good candidate for surgery due to elevated risk (logistic EuroSCORE 24%). The procedure alone was uncomplicated, performed through the transfemoral access with a 29 mm CoreValve bioprosthesis. Unfortunately, 20 days after the procedure the patient’s condition suddenly deteriorated, with symptoms of acute heart failure and chest pain, followed by shock and with accompanying sepsis. Based on clinical findings, inverted T waves in ECG precordial leads, elevated levels of troponin, echocardiography with new regional wall motion abnormalities and angiography (normal coronary arteries) the diagnosis of stress cardiomyopathy (tako-tsubo like cardiomyopathy) was made. After intensive pharmacological treatment with haemodynamic monitoring the patient’s condition gradually improved. Echocardiography revealed gradual regression of regional wall motion abnormalities and improvement of left ventricular function. The case indicates the possibility of less typical complications of TAVI, like tako-tsubo syndrome, and should be considered in differential diagnosis of chest pain in patients undergoing this procedure.